Elicitation of Salicylic Acid on Secondary Metabolite Production and Antioxidant Activity of In Vitro Musa acuminata L. cv. ‘Gros Michel’ Shoots - Jirakiattikul*, Yaowapha; Rithichai, Panumart; Songsoem, Kanokwan; Itharat, Arunporn (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2021)
In vitro Musa acuminata L. cv. ‘Gros Michel’ is a potential alternative source of secondary metabolites but low yield was obtained. Elicitation is used to increase secondary metabolite production by many plant species. The objective of this study was to investigate the effect of salicylic acid (SA), an elicitor, on secondary metabolite accumulation and antioxidant activity in shoot cultures of M. acuminata cv. ‘Gros Michel’. Shoots of one centimeter in length were cultured for four weeks on Murashige and Skoog (MS) medium supplemented with 22.19 µM 6-benzyladenine (BA) and 0, 100, 200, or 300 µM SA. The results showed that SA was effective in enhancing the secondary metabolite production and antioxidant activity of M. acuminata cv. ‘Gros Michel’ shoots. The contents of secondary metabolites and antioxidant activity were significantly different among the treatments. Shoots treated with 100 µM SA exhibited the greatest accumulation of total saponins (263.86±0.42 mg diosgenin/ g dry extract), total phenolics (124.44±8.39 mg GAE/g dry extract), and total flavonoids (105.26±6.43 mg CE/g dry extract). These were 1.27, 1.25, and 1.34 times that of the control. The strongest antioxidant radical scavenging was also observed from 100 µM SA treated shoots (DPPH EC50 value of 9.79±0.86 µg/ml and ABTS EC50 value of 86.66±1.50 µg/ml). Keywords: antioxidant; elicitor; phenolics; salicylic acid; saponins *Corresponding author: Tel.: (+66) 8545092 E-mail: yjirakia@tu.ac.th